Sustainable shift: institutional challenges for the environment in Malaysia - Adnan A. Hezri (Universiti Kebangsaan Malaysia, 2011)
Sustainable development is a global challenge. It is a systemic one and is deeply embedded in the pattern of economic production and consumption. The ‘shift’ towards sustainable development requires an institutional change, and one which requires a long-term perspective. The article traces the evolution of environmentalism, demarcated into three main waves namely, nature protection, governmental reform, and green investment. It also discusses the nature of institutions through cursory review of definitions and principles for institutional reform. In comparison to ‘organisation,’ ‘institution’ is broader, durable and persistent, so much so that its ‘hardware’ and ‘software’ must be considered in tandem. Next, a cursory assessment of Malaysia’s sustainability policy performance is also presented. The final part of the article asks what are the institutional challenges for the sustainable shift in Malaysia? Taken together, weak implementing agencies, conflicting Federal-State relationship, feeble environmental advocacy, and research that is policy-irrelevant, demand a concerted effort in thinking institutionally to find solutions to unsustainable development trajectory